Compliance of Standard Signages Provision based on Visual Inspection at Primary School Zones in Johor - Sanik, Mohd Erwan; Bujang, Hazirah; Hamid, Nor Baizura; Idris, Nur'ain (Recent Trends in Civil Engineering and Built Environment, 2025)
This study investigates the compliance of road signage with standard safety provisions in primary school zones across Johor, Malaysia. With school zones being a focal point for child pedestrian safety, the presence of adequate signage is crucial to minimizing accidents and promoting compliance with traffic laws. Using a road safety audit approach, including both on-foot and drive-through inspections, data were collected from ten schools located near major roads. The study followed the MeTRA guideline to assess the availability and condition of road signage. Results showed a concerning 50% compliance rate, with only one school meeting all signage requirements. The findings reveal recurring issues such as missing signs, inadequate road infrastructure, and poor pedestrian facilities, posing significant risks to schoolchildren. The study concludes that both improving the physical road environment and educating students on safe road practices are essential steps towards enhancing road safety in school zones.